A novel bi-functional double-layer rGO–PVDF/PVDF composite nanofiber membrane separator with enhanced thermal stability and effective polysulfide inhibition for high-performance lithium–sulfur batteries. Issue 29 (10th July 2017) - Zhu, Pei; Zhu, Jiadeng; Zang, Jun; Chen, Chen; Lu, Yao; Jiang, Mengjin; Yan, Chaoyi; Dirican, Mahmut; Kalai Selvan, Ramakrishnan; Zhang, Xiangwu
Abstract : A novel, bi-functional double-layer reduced graphene oxide (rGO)–polyvinylidene fluoride (PVDF)/PVDF membrane was fabricated by a simple electrospinning technique and was used as a promising separator for lithium–sulfur batteries. Abstract : A novel, bi-functional double-layer reduced graphene oxide (rGO)–polyvinylidene fluoride (PVDF)/PVDF membrane was fabricated by a simple electrospinning technique and was used as a promising separator for lithium–sulfur batteries. This double-layer membrane separator delivers two different functionalities: (i) the porous PVDF nanofiber framework in both rGO–PVDF and PVDF layers provides good thermal stability and maintains the structural integrity of the separator; and (ii) the conductive rGO–PVDF layer serves as a polysulfide inhibitor and ensures the fast transfer of lithium ions. Compared to conventional polypropylene membrane separators, this new separator design can significantly enhance the cycling stability and rate capability of the incorporated lithium–sulfur batteries. Overall, it is demonstrated that this new double-layer rGO–PVDF/PVDF composite membrane separator opens an alternate avenue in the structural design of high-performance lithium–sulfur batteries in dealing with multiple challenges.